2021
DOI: 10.1371/journal.pone.0245448
|View full text |Cite
|
Sign up to set email alerts
|

Risk of 28-day readmissions among stroke patients in Malaysia (2008–2015): Trends, causes and its associated factors

Abstract: Background and objectives Risk of readmissions is an important quality indicator for stroke care. Such information is limited among low- and middle-income countries. We assessed the trends for 28-day readmissions after a stroke in Malaysia from 2008 to 2015 and evaluated the causes and factors associated with readmissions in 2015. Methods Using the national hospital admission records database, we included all stroke patients who were discharged alive between 2008 and 2015 for this secondary data analysis. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
4
0
3
Order By: Relevance
“…All research uses secondary data from patient medical records. (Ang et al, 2021;Bjerkreim, Khanevski, Glad, et al, 2018;Bjerkreim, Khanevski, Selvik, et al, 2018;Boehme et al, 2018;Chuang et al, 2005;Kilkenny et al, 2020;Swanson & Moger, 2019;Vahidy et al, 2017;Wen et al, 2018b;Zhang et al, 2019a) The results show that the incidence of readmissions for stroke patients ranges from 10%-28% each year, where readmissions for stroke patients can occur 7-30 days after the patient is discharged. The causal factors related to the incidence of readmission in stroke patients can be concluded to be divided into 2 factors, namely factors that cannot be prevented and factors that can be prevented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All research uses secondary data from patient medical records. (Ang et al, 2021;Bjerkreim, Khanevski, Glad, et al, 2018;Bjerkreim, Khanevski, Selvik, et al, 2018;Boehme et al, 2018;Chuang et al, 2005;Kilkenny et al, 2020;Swanson & Moger, 2019;Vahidy et al, 2017;Wen et al, 2018b;Zhang et al, 2019a) The results show that the incidence of readmissions for stroke patients ranges from 10%-28% each year, where readmissions for stroke patients can occur 7-30 days after the patient is discharged. The causal factors related to the incidence of readmission in stroke patients can be concluded to be divided into 2 factors, namely factors that cannot be prevented and factors that can be prevented.…”
Section: Discussionmentioning
confidence: 99%
“…(Bjerkreim, Khanevski, Glad, et al, 2018;Boehme et al, 2018;Miller et al, 2019) The five most common diagnoses or causes for readmission after stroke were recurrent stroke (32.1%), followed by stroke complications such as pneumonia (13.0%), sepsis (4.8%) and urinary tract infection (UTI) ( 2 .9%) and ischemic heart disease (3.7%). (Ang et al, 2021) Based on the results of other studies, it is also stated that a high level of dependence on patients when they are discharged can also be a risk factor for readmissions in patients. Patients with lower functional ability to fulfill their activity daily needs, who still have a high NIHSS score at discharge, may experience higher readmissions < 30 days post discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Hasil penelitian dalam kurun waktu 7 tahun di Taipei, dalam waktu 28 hari setelah pulang ke rumah, 11-13% pasien akan mengalami lagi readmisi setiap tahunnya, terbanyak adalah diagnosis stroke iskemik (Ang et al, 2021). Terdapat beberapa faktor yang menyebabkan readmisi pasien tersebut, dimana usia, jenis kelamin, lama dirawat bukan merupakan faktor yang berpengaruh terhadap readmis (Wu et al, 2007).…”
Section: Pembahasanunclassified
“…Several studies on the outcome of hospital admissions for acute stroke have shown that 36.2% were discharged independent while 53.1% had functional dependence. Between 2008 and 2015, re-admission rates at 28 days post-discharge range from 11 to 13%, usually for stroke recurrence and infection, with a higher risk among those with intracerebral haemorrhage [ 10 , 11 ].…”
Section: Stroke Burden and Stroke Epidemiologymentioning
confidence: 99%